Kidney Diseases - Polatjonov Muhammaddiyor (Zien Journals, 2025)
This article describes the anatomical location, physiological importance, and diseases of the kidneys. It discusses the challenges of late diagnosis, the link between kidney diseases and cardiovascular complications, and the economic difficulties of treatment such as hemodialysis. The main causes of kidney diseases are identified as obesity, diabetes mellitus, high blood pressure, harmful habits, and metabolic disorders. The article also highlights symptoms of kidney dysfunction and kidney stone disease (nephrolithiasis).
Keywords: Kidney anatomy; kidney diseases; nephrology